2022
DOI: 10.1038/s41598-022-17288-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel transport properties of the α-T3 lattice with uniform electric and magnetic fields

Abstract: We report a theoretical study of electronic transport properties of α-T3 lattice nanoribbons in the presence of uniform electric and magnetic fields. Landau levels with an unexcepted fashion are obtained in the system, and unique flat bands are observed due to the crossed electric and magnetic fields. We found that the nondispersive flat band of α-T3 lattice is distorted and split to many dispersive energy levels when electric and magnetic fields are applied. A double constriction structure of α-T3 lattice is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We consider the α − T 3 lattice of the zigzag and armchair boundary in the two-terminal and four-terminal systems, respectively. In the tight-binding representation, the Hamiltonian of the α − T 3 lattice nanoribbons is expressed as [46,55]…”
Section: Model and Methodsmentioning
confidence: 99%
“…We consider the α − T 3 lattice of the zigzag and armchair boundary in the two-terminal and four-terminal systems, respectively. In the tight-binding representation, the Hamiltonian of the α − T 3 lattice nanoribbons is expressed as [46,55]…”
Section: Model and Methodsmentioning
confidence: 99%
“…the energy range for which a nonzero optical conductivity exists, the wave function components in Eqs. ( 8)- (10) actually quantify the magnitude of the frequency dependence in the same optical conductivity.…”
Section: Electronic States With An Irradiation-modified Bandstructurementioning
confidence: 99%
“…(B4) for matrix diagonalization, can be built from the component of eigen-function defined in Eqs. ( 8)- (10), leading to Appendix C: Green's functions and spectral functions for a gapped dice lattice.…”
Section: Appendix B: General Formalism For Optical Conductivitymentioning
confidence: 99%
“…Moreover, the recent experiment has reported that the Hg 1−x Cd x Te at critical doping can be mapped into the α−T 3 lattice model with α 1 3 = [23]. The additional atoms of the α−T 3 leads to many fascinating properties [24][25][26][27]. One peculiar feature is the nondispersed fat band, as shown in figure 1(c) where an additional flat band that passes through the Dirac point.…”
Section: Introductionmentioning
confidence: 99%